If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 + -21x = 63 + -7y Solving 42 + -21x = 63 + -7y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -21x = 63 + -42 + -7y Combine like terms: 42 + -42 = 0 0 + -21x = 63 + -42 + -7y -21x = 63 + -42 + -7y Combine like terms: 63 + -42 = 21 -21x = 21 + -7y Divide each side by '-21'. x = -1 + 0.3333333333y Simplifying x = -1 + 0.3333333333y
| (6xy+7)dx+(3x^2-2)dy=0 | | 6x+9-x+19= | | 4x+10=-42-8x | | 3n=34 | | 17x-2x=7x+11 | | 7x+13=3x+65 | | 4x+38=180 | | 2(x-3)(x-3)+3=13 | | 2(x-3)+3=13 | | x^4-x^3-2x^2+4x-24=0 | | (X^2+24)= | | 3x^2-11x-3=-x^2 | | Un=5+(0.1n-0.1) | | Un=5+(0.1n+0.1) | | Cos(5x)-cos(9x)=0 | | z^2-(3-2i)z+(5-5i)=0 | | 6x=n+4 | | 4x^2+12x+9=49x | | 4x^3+12x+9=49x | | -6.8(7.9+1.2*-7.3)+3.7=4.2*-7.3+40.90016 | | 1/8+2/3= | | 1/3+2/3= | | 5y+11=6 | | -6.8(7.9+1.2x)+3.7=4.2x+40.90016 | | x^2-1x+40=0 | | (m+2n+1)(m-n+2)=5 | | x^2+12x+35x=0 | | 4x+13=-29-2 | | x+2x+6x+18x=160 | | 7(x*5)=9(6+4) | | 4m^2+4x=60 | | 3(2p-1)=8 |